Theme and authenticity: experiencing heritage at The Venetian. Issue 2 (27th July 2020) - Soligo, Marta; Abarbanel, Brett
Abstract : Purpose: This article analyzes the concepts of experience economy and promotion of authenticity at The Venetian Hotel and Casino in Las Vegas by exploring the resort's tangible and intangible heritage use in design and marketing strategies. Design/methodology/approach: This qualitative study conducts a content analysis of marketing material, historical documents, and site observations. Findings: Visitors' active involvement, combined with The Venetian's use of tangible and intangible heritage, is used in creating an authentic themed experience. In addition, our study suggests that authenticity constitutes a key concept for today's hospitality industry. Research limitations/implications: This study centers on a single case study, and requires adjustments in order to be replicated. However, The Venetian represents one of the most prominent models followed by the hospitality industry worldwide. Practical implications: This analysis provides a baseline for comparison among resorts that have theming but do not integrate it in the same way, or in general, to other professionals and academics considering themed experiences. Social implications: The manuscript centers on several aspects that are being debated in numerous fields, from business to sociology, such as customers' desire for authentic experiences through the creation of themed attractions. Originality/value: This research fills a gap in hospitality marketing research into authenticity and themed experience by investigating how The Venetian Hotel and Casino uses the heritage of another, tourism-focused city (Venice) to promote itself. The investigation uncovers how themed attractions in hospitality create an experience-based involvement that centers on the authenticity of the theme (in our case cultural heritage) they replicate.